Development of a simulation platform of all-electric aircraft on-board systems for energy management studies. (30th March 2017) - Schettini, F.; Denti, E.; Di Rito, G.
ABSTRACT: This paper deals with the development of a simulation platform for the dynamic analysis of systems characterised by different physical domains. The research has been carried out in the context of the EC-funded Clean Sky Joint Technology Initiative (Green Regional Aircraft/All-Electric Aircraft domain). In particular, the objective of the research is focused on the on-board systems of new All-Electric Aircraft, where a crucial design point is related to the electrical energy management. In the "all-electric" concept, where pneumatic and hydraulic power systems are eliminated to improve aviation costs and environmental impact, the dynamics of electrical power absorptions is to be characterised and managed to avoid excessive peaks with respect to generators capabilities. The paper describes the architecture of a Matlab/Simulink simulation platform developed in order to design and validate of the electrical energy management logics, which lead up to 32% reduction of the maximum power request for the case study considered. Thanks to an approach based on a mixing of co-simulation and S-function compiling, the platform integrates models coming from different environments (AMESim, Dymola/Modelica), and developed by various partners/specialists.